Double-blind, placebo controlled, crossover study of lamotrigine in treatment resistant partial seizures. Issue 5 (May 1993) - Schapel, G J; Beran, R G; Vajda, F J; Berkovic, S F; Mashford, M L; Dunagan, F M; Yuen, W C; Davies, G
Abstract : The results of a multicentre, randomised, double-blind, placebo controlled, crossover trial of lamotrigine as add-on therapy in patients with partial seizures poorly controlled by established antiepileptic drugs (AEDs) are presented. The study consisted of two 12 week treatment periods each followed by a four week washout period. During the lamotrigine treatment phase, patients received 150 mg or 300 mg daily dose depending on their concomitant AEDs to achieve concentrations in the range 1-3 mg/L. Forty one patients were entered at four centres and all patients entered completed the study. There was a highly significant (p < 0.001) decrease in total seizure counts on lamotrigine compared with placebo. Overall, 22% of patients experienced at least a 50% reduction in the total numbers of all seizures types on lamotrigine, compared with none on placebo. When the total numbers of partial seizures (simple and complex partial) were analysed there was also a significant (p < 0.05) reduction in seizure counts on lamotrigine compared with placebo. When total numbers of secondarily generalised seizures were compared the trend for a reduction in this seizure type did not achieve significance (0.05 < p < 0.1). Concomitant AED plasma concentrations were virtually unchanged. It is concluded that lamotrigine is an effective AED in the treatment of therapy-resistant partial seizures.